MODEL PENGENTASAN SIKAP PROKRASTINASI AKADEMIK (STUDI PENGEMBANGAN BERBASIS COGNITIVE BEHAVIOR THERAPY) - Rahmatia Rahmatia; Nur Halim Abdul Rahman (Program Studi bimbingan Konseling PPs UNM Makassar, 2015)
This study aims to determine (1) description of the demand level of reduction model of academic procrastination attitude on high school students in Makassar. (2) Description of a hypothetical model of academic procrastination attitude alleviation based on cognitive behavior therapy. (3) Description of the academic procrastination attitude alleviation model, based on cognitive behavior therapy which had developed. This study used the approach and development of research as well as qualitative and quantitative methods. The study population was high school in the city of Makassar with a sample of 12 schools. The results showed: (1) the demands’ level of academic procrastination attitude reduction model of high school students in Makassar at the high category; (2) the hypothetical model is the beginning of the preparation of academic procrastination attitude alleviation models. The model was developed based on the need assessment. The model consists of several components such as rational, objectives, scope, target population, the basic assumptions, the working principle, system support services, the role of counselor, procedure implementation, evaluation model, and the model guidelines; (3) the developed models are models that have gone through the stage of model validation both by BK experts and practitioners in schools so that the model has been tested in content and descriptively. Therefore, the developed model generated in this study is a model that is ready to be used in schools to help students in eliminating academic procrastination habit.